Halomax® as a method for chromatin staining in cat sperm - Sjödahl, Agnes (2016)
Wild felids all over the world are threatened by extinction. As a part of the preservation task concerning those species, in zoos as well as in situ in their wild habitat, the use of assisted reproduction technology (ART) is explored, e. g. artificial insemination (AI) and in vitro fertilization (IVF). For practical use there is a need for feasible and reliable methods for collecting, evaluating, storing and eventually using gametes for fertilizing embryos, and hopefully establishing and maintaining pregnancy. It is impractical to use wild felids for extensive research because of the scant numbers of individuals, accessibility etcetera. Therefore the domestic cat frequently serves as a model animal for research. This student work focus on evaluating a certain method for measuring DNA fragmentation in cat spermatozoa, Halomax®. We thawed epididymal sperm from 12 cats, one from corpus epididymidis and one from cauda epididymidis for each cat except one. The measurements were compared to results in a PhD-project, showcasing the DNA fragmentation index (%DFI); Acridine orange using both epi-fluorescence microscope and flow cytometry. It resulted in a significant difference in the DFI between spermatozoa from corpus or cauda using Halomax® but no significant correlations between methods were found. The discrepancy between these methods has been noted in earlier studies and one of the theories states that the methods could be measuring different kinds of strand breaks in the DNA. The difference between epididymal regions has also been seen in previous studies, and is believed to be due to the maturing process of spermatozoa or some kind of phagocytosis of defective spermatozoa.